2D Metal‐Organic Framework Based on the Functionalized Anthracene Derivative as A Dual‐Functional Luminescent Probe for Fe3+ and Ascorbic Acid. Issue 29 (3rd August 2022) - Chen, Zi‐Yi; Li, Peng‐Cheng; Guo, Cui; Chen, Xiao‐Huan; Liu, Bing‐Jie; Zou, Hui‐Jing; Liang, Wen‐Jie; Xu, Hai
Abstract: Two‐dimensional (2D) materials are newly developed for their thickness‐dependent physical and chemical properties. The major characteristic of this type of material is that the planar structure flaunts a large surface‐to‐volume ratio, thereby providing a platform for straightforward and easy functionalization with chemical moieties, which prompting us to use it as a chemical sensor. We designed and synthesized two types of 2D metal‐organic frameworks based on the functionalized anthracene derivative 4, 4′‐(anthracene‐9, 10‐diylbis(ethyne‐2, 1‐diyl))dibenzoic acid (H2 L), [Pb(L)(DMF)] (denoted as Pb‐MOF) and [Sm(L)(HCO2 )(DMF)] (denoted as Sm‐MOF). These two materials are great sensors for probing Fe 3+ and ascorbic acid (AA) with the low concentration according to "color‐change recover" effect. Fe 3+ was captured by MOF and this quenching mechanism was investigated using luminescence, UV‐vis, XPS, and lifetime studies. Abstract : Two types of 2D metal‐organic frameworks based on the functionalized anthracene derivative 4, 4′‐(anthracene‐9, 10‐diylbis(ethyne‐2, 1‐diyl))dibenzoic acid (H2 L) were developed as great sensors for probing Fe 3+ and ascorbic acid (AA) with excellent sensitivity and selectivity. In addition, these two materials provide a platform for straightforward and easy functionalization with chemical moieties and have promising potential to be a useful tool as chemical sensors.